Diabetic ketoacidosis in a pediatric intensive care unit - Lopes,Clarice L.S. (2017)
Abstract Objective: To describe the characteristics of children aged 0-14 years diagnosed with diabetic ketoacidosis and compare the following outcomes between children with prior diagnosis of type 1 diabetes mellitus and children without prior diagnosis of type 1 diabetes mellitus length of hospital stay, severity on admission, insulin dosage, time of continuous insulin use, volume of fluids infused during treatment, and complications. Methods: A retrospective descriptive study with review of medical records of patients admitted to the pediatric intensive care unit of a referral hospital from June 2013 to July 2015. The following data regarding 52 admissions were analyzed: age, sex, weight, body surface area, signs, symptoms and severity on admission, blood gas, blood glucose, glycated hemoglobin, serum osmolarity, and index of mortality. The insulin dosage, time of continuous insulin use, volume administered in the expansion phase and in the first 24 h, length of stay, and complications such as electrolyte disturbances, hypoglycemia, cerebral edema, and death were compared between the two groups. Results: Patients without a previous diagnosis of DM1 were younger at admission, with mean age of 8.4 years (p < 0.01), reported more nausea or vomiting, polydipsia and polyuria, and showed more weight loss (p < 0.01). This study also observed a higher prevalence of hypokalemia (p < 0.01) and longer hospital stay in this group. Conclusions: No differences in severity between groups were observed. The study showed that children without prior diagnosis of type 1 diabetes mellitus were younger at admission, had more hypokalemia during the course of treatment, and had greater length of hospital stay.